2019
DOI: 10.1002/pep2.24139
|View full text |Cite
|
Sign up to set email alerts
|

New insights into differential aggregation of enantiomerically pure and racemic Aβ40 systems

Abstract: Racemic mixtures frequently display properties that are different from those associated with their enantiopure counterparts, and are often characterized by higher propensity to form aggregates. Our previous research established that mixing of the enantiomers of Alzheimer amyloid β (Aβ) 42 peptides is an effective strategy to induce an oligomer‐to‐fibril conversion, which puts Aβ42 into a substantially less toxic state. Here, new insights into this chiral inactivation effect are presented. In addition to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 22 publications
6
40
0
Order By: Relevance
“…[ 10,11 ] The Raskatov lab developed Aβ Chiral Inactivation (Aβ‐CI) as an approach to induce an oligomer‐to‐fibril transition to suppress peptide toxicity, using mirror‐image Aβ42 as the molecular mirror‐image chaperone of the natural all‐L Aβ42 peptide. [ 12,13 ] Consistent trends were observed for the Aβ40 system, [ 14 ] and subsequent DFT‐based work found the rippled parallel LVFFA dimer to be favored over three distinct, experimentally observed pleated frameworks. [ 15 ] The rippled cross‐β topography has thus burgeoned as a valuable design principle for materials and in biomedical applications.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…[ 10,11 ] The Raskatov lab developed Aβ Chiral Inactivation (Aβ‐CI) as an approach to induce an oligomer‐to‐fibril transition to suppress peptide toxicity, using mirror‐image Aβ42 as the molecular mirror‐image chaperone of the natural all‐L Aβ42 peptide. [ 12,13 ] Consistent trends were observed for the Aβ40 system, [ 14 ] and subsequent DFT‐based work found the rippled parallel LVFFA dimer to be favored over three distinct, experimentally observed pleated frameworks. [ 15 ] The rippled cross‐β topography has thus burgeoned as a valuable design principle for materials and in biomedical applications.…”
Section: Introductionmentioning
confidence: 58%
“…Cross‐β dimers were constructed from Pauling‐Corey coordinates, as described previously. [ 14 ] The topographies used to construct DFT input structures are shown in Figure 1, and have been deposited as part of the Supporting Information. The pentapeptidic strings were N‐terminally acetylated and C‐terminally amidated and t Bu sidechains added geometrically at all C α positions using Molden.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Previous research by Dutta et al reported a low-energy DFToptimized rippled LVFFA:lvffa dimer structure. [9] This published geometry was used as initial input structure here, but it was possible to locate a lower-energy rippled cross-β dimer structure (see Computational Details). This dimeric system was fully re-optimized and determined to be energetically favored by 4.2 kcal/mol over the most stable of the pleated structures considered in this study, that is, (LVFFA) 2 Aβ42 5oqv , rot.A .…”
Section: Comparison Of Pleated and Rippled Systems And Mechanistic Immentioning
confidence: 99%
“…[8] Our more recent work showed that racemic Aβ40 fibrils were distinct from enantiopure ones. [9] Morphologically, fibrils formed from enantiopure Aβ40 display a twist, whereas those made from racemic Aβ40 did not. Also, there was a notable difference in width of the mature fibrils, which were approximately two times as wide in the enantiopure case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation